Skeletal remodelling of α-substituted cyclic eneformamides to α-ketonyl cyclic amines. (4th September 2020) - Beng, Timothy K.; Garcia, Jorge; Smith, Meagan; Orellana, Alexis O.
Abstract : A modular dehomologation strategy, which skeletally remodels cyclic α-substituted eneformamides to one-carbon shorter α-ketonyl saturated cyclic amines is described. Abstract : A modular dehomologation strategy, which skeletally remodels cyclic α-substituted eneformamides to one-carbon shorter α-ketonyl saturated cyclic amines is described. The approach hinges on N -iodosuccinimide-assisted C–halogen bond formation followed by C–N bond cleavage to arrive at α-iodo ketones, which undergo base-mediated cyclization. An intramolecular C(sp 3 )–H amination of in situ -generated N -iodo tethered ketones also affords the desired α-ketonyl cyclic amines. The transformation is applicable to an array of α-functionalized eneformamides, but some chemoselective challenges were encountered with a few substrates.